Study skills, student attitude and study group as predictors of study habits of secondary school students in Itesiwaju local Government, Oyo State (2016)
"The study examined study skills, student attitude and study group as predictors of study habits of secondary school students in Itesiwaju Local government Area, Oyo State. A descriptive research design was employed in the study. Three hundred senior secondary school 2 (SS 2) students were randomly selected from six schools out of ten public secondary schools in Itesiwaju Local government Area, Oyo State for data collection. Their age ranged between 10 and 24 years old with mean age of 17.4 and standard deviation of 1.68. Three research questions were answered. The dato were analyzed using Pearson's Product Moment Correlation and Multiple Regression Analyses. The results showed that study skills was the most significant predictor of study habits followed by the student attitude. It was recommended that students should be assisted to build good study habits as early as they start school by incorporating study skills acquisition training and other student intervention strategies into school curriculum."